2008
DOI: 10.21608/jvmr.2008.77846
|View full text |Cite
|
Sign up to set email alerts
|

Some parasitic and bacterial causes of liver affections in ruminants

Abstract: In the present study, a total number of 1576 livers of ruminants, including cattle (924), sheep (487) and camels (165) were examined for detection of different pathogenic agents. Among those, a number of 58 cases (3.68 %) were infected with both parasites and bacteria. Out of this number, 3 cases only (0.19 %) were infected with bacterial species (Lactobacillus lactis lactis), 31 cases (1.97 %) were infected with parasitic stages only and a number of 24 cases (1.52 %) were co-infected with both bacteria and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
(5 reference statements)
0
9
1
Order By: Relevance
“…Confirmed to our results, [22] could not detect hydatid cyst from any of the examined slaughtered camels. Also, some authors recorded nearly similar percentage of hydatid cysts as, [23] (8.8%) [24] who revealed that the overall annual prevalence rates of camel infection were 5.5% (1992), 6.1% (1993), 6.7% (1994), 8.2% (1995) and 4.3% (1996), [25] (4.9%), [26] (9%) and [27] (5.5%). On the other side, the obtained results were lower than that recorded by [28] (20,4%), [29] who recorded 50% in Northern of Guinea zone and 55.5% in Sudan zone, [29] (40%), [30] (16%), [31] (20.7%).…”
Section: Resultsmentioning
confidence: 90%
“…Confirmed to our results, [22] could not detect hydatid cyst from any of the examined slaughtered camels. Also, some authors recorded nearly similar percentage of hydatid cysts as, [23] (8.8%) [24] who revealed that the overall annual prevalence rates of camel infection were 5.5% (1992), 6.1% (1993), 6.7% (1994), 8.2% (1995) and 4.3% (1996), [25] (4.9%), [26] (9%) and [27] (5.5%). On the other side, the obtained results were lower than that recorded by [28] (20,4%), [29] who recorded 50% in Northern of Guinea zone and 55.5% in Sudan zone, [29] (40%), [30] (16%), [31] (20.7%).…”
Section: Resultsmentioning
confidence: 90%
“…In this regards, slaughter houses can provide an excellent opportunity for detecting pathological lesions of both economic and public health importance (Vecerck et al, 2003;Raji et al, 2010). Frequent abattoir surveys have been conducted in different countries to detect the gross and microscopic lesions in lungs, liver, spleen and kidney of cattle (El-Dakhly et al, 2007;Mwabonimana, 2008;Belkhiri et al, 2009;Raji et al, 2010;Alawa et al, 2011). However, the gross and microscopic lesions usually indicate the advanced stages of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In case of chronic fascioliasis, there was biliary and portal cirrhosis due to proliferation of fibrous connective tissue accompanied by infiltration of mononuclear cells, thickening and hyperplastic changes in the lining epithelium of the bile duct. This may be due to the response of macrophages and lymphocytes in the necrotic areas during the later stages of fascioliasis and the merging fibrous tissues into the healing sites ( El-Dakhly et al, 2008 , Sayed et al, 2008 ). Fibrous cholangitis was observed in five cases.…”
Section: Discussionmentioning
confidence: 99%